Hamd in Haiku: An Overview - Fouzia Anjum; Muhammad Afzal Hameed (بازیافت, 2023)
<!--StartFragment-->   Hamdia poetry was started at the beginning of Urdu literature. Hamd has been a part of every poetical work for a long period of time. Gradually Hamd not only presented itself as a separate kind but also appeared as a prominent genre of Urdu poetry. A large collection of Hamdia poetry by different poets has been published time to time. Today Hamdia poetry is being written in ancient, modern, eastern and western genres. This article deals with the Hamdia poetry written the particular genre Haiko. <!--EndFragment-->